Early neutralizing IgG response to Chikungunya virus in infected patients targets a dominant linear epitope on the E2 glycoprotein - Kam, Y.W.; Lum, F.M.; Teo, T.H.; Lee, W.W.L.; Simarmata, D.; Harjanto, S.; Chua, C.L.; Chan, Y.F.; Wee, J.K.; Chow, A.; Lin, R.T.P.; Leo, Y.S.; et al. (2012)
Chikungunya virus (CHIKV) and related arboviruses have been responsible for large epidemic outbreaks with serious economic and social impact. The immune mechanisms, which control viral multiplication and dissemination, are not yet known. Here, we studied the antibody response against the CHIKV surface antigens in infected patients. With plasma samples obtained during the early convalescent phase, we showed that the naturally-acquired IgG response is dominated by IgG3 antibodies specific mostly for a single linear epitope E2EP3. E2EP3 is located at the N-terminus of the E2 glycoprotein and prominently exposed on the viral envelope. E2EP3-specific antibodies are neutralizing and their removal from the plasma reduced the CHIKV-specific antibody titer by up to 80. Screening of E2EP3 across different patient cohorts and in non-human primates demonstrated the value of this epitope as a good serology detection marker for CHIKV infection already at an early stage. Mice vaccinated by E2EP3 peptides were protected against CHIKV with reduced viremia and joint inflammation, providing a pre-clinical basis for the design of effective vaccine against arthralgia-inducing CHIKV and other alphaviruses.